Community Empowerment: The Need for a Bumdes Strategy in Improving Welfare - Mayarni; Surya Arfan; Mimin Sundari Nasution; Zulkarnaini (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
This study aims to determine community empowerment based on Kepenghuluan-owned enterprises (Bumkep) in Kepenghuluan Sinaboi, Rokan Hilir Regency, Riau Province. The problem of social welfare development related to various other development fields is the low economic level of society. This is characterized by unemployment, underdevelopment and helplessness. Therefore, it takes the role of the Kepenghuluan Sinaboi to increase community empowerment by utilizing the Sinaboi BUMKEP. This research chooses a descriptive research with a qualitative approach. The results of this study found that the local community still lacks information about the utilization of local potential, the empowerment that is participatory is very minimal.